Thermal stress impairs photophysiology and redox balance in the kelp Lessonia spicata - Navarrete, Camilo; Troncoso, Macarena; Lavergne, Céline; Molina, Verónica; Celis-Plá, Paula S. M. (Frontiers in Plant Science, 2025)
Warming oceans are reshaping coastal ecosystems, yet the thermal sensitivity of many foundation macroalgae remains poorly constrained. Under SSP2-4.5, sea surface temperatures are expected to rise by ~2.7 °C by 2100, with unknown consequences for the canopy-forming kelp Lessonia spicata. We exposed thalli to control (15 °C) and warming (18 °C) conditions for 14 days to simulate near-future thermal scenarios, assessing photophysiology, oxidative stress and pigment composition. Warming caused marked declines in Fv/Fm and ETRmax and increased NPQmax, signaling reduced photochemical efficiency and enhanced thermal energy dissipation. Simultaneously, pigment concentrations decreased, ROS and MDA accumulated, and antioxidant capacity dropped, indicating rapid disruption of cellular redox homeostasis. Our results demonstrate that even modest warming consistent with mid-century projections triggers immediate photophysiological impairment and oxidative stress in L. spicata. These mechanistic insights highlight potential vulnerability of kelp forests in central Chile as ocean temperatures continue to rise.